Corporate responsibility in implementing CSR during the Covid-19 pandemic - erytatina, Erytatina Sukmawanti (COMMICAST, 2022)
Corporate social responsibility (CSR) is a form of the company’s concern for the company’s environment through various activities carried out in the context of conservation, development participation, and various other social responsibilities. This study aims to determine the CSR challenge program and how the solutions that PT. SHRAP Electronics  Indonesia do to solve these challenges. The type of research used is descriptive qualitative research, namely qualitative research that describes in detail the portrait of the actual conditions that occurred. Where to explain these conditions using interactive analysis Miles and Huberman. Data collection techniques with in-depth interviews, direct observation and literature study. Interviews were conducted with Research Informants as parties who understand and understand the process of implementing CSR programs that are implemented. The results of this study indicate that the CSR program of PT. SHARP Electronics Indonesia has a positive and significant impact on participation in providing social response programs in the midst of the COVID-19 pandemic so as to create a positive corporate image.